The Influence of Constructive Conflict Resolution Styles and Perceived Stress On Marriage Satisfaction Among Dual Earner Couples - Yosza, Amearah Bellarosa; Sovitriana, Rilla (Dinasti Health and Pharmacy Science, 2023)
This study aims to investigate the influence of constructive conflict resolution styles and perceived stress in marital satisfaction among dual-earner couples in DKI Jakarta. A quantitative method using incidental sampling is used to select respondents who meet specific criteria. Questionnaires were distributed to 117 married respondents who have been married for 1 to 5 years and are dual-earners; both of whom are employed in DKI Jakarta. The instruments used in this study include the Conflict Resolution Styles Inventory (CRSI), Perceived Stress Scale (PSS), and ENRICH Marital Satisfaction Scale (EMS). Results showed constructive conflict resolution style indicated a p-value < 0,05 with R2 value of 8,3%. This means that Ha1 is accepted, indicating a significant influence of constructive conflict resolution style on marital satisfaction. The p-value for perceived stress < 0,05 with R2 value of 10,4%, meaning Ha2 is accepted. The results from the multiple linear regression analysis show that both constructive conflict resolution styles and perceived stress significantly influence marital satisfaction.